Evaluation of Lower-Dose Spiral Head CT for Detection of Intracranial Findings Causing Neurologic Deficits - Fletcher, J.G.; DeLone, D.R.; Kotsenas, A.L.; Campeau, N.G.; Lehman, V.T.; Yu, L.; Leng, S.; Holmes, D.R.; Edwards, P.K.; Johnson, M.P.; Michalak, G.J.; Carter, R.E.; et al. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Despite the frequent use of unenhanced head CT for the detection of acute neurologic deficit, the radiation dose for this exam varies widely. Our aim was to evaluate the performance of lower-dose head CT for detection of intracranial findings resulting in acute neurologic deficit.MATERIALS AND METHODS: Projection data from 83 patients undergoing unenhanced spiral head CT for suspected neurologic deficits were collected. Cases positive for infarction, intra-axial hemorrhage, mass, or extra-axial hemorrhage required confirmation by histopathology, surgery, progression of findings, or corresponding neurologic deficit; cases negative for these target diagnoses required negative assessments by two neuroradiologists and a clinical neurologist. A routine dose head CT was obtained using 250 effective mAs and iterative reconstruction. Lower-dose configurations were reconstructed (25-effective mAs iterative reconstruction, 50-effective mAs filtered back-projection and iterative reconstruction, 100-effective mAs filtered back-projection and iterative reconstruction, 200-effective mAs filtered back-projection). Three neuroradiologists circled findings, indicating diagnosis, confidence (0–100), and image quality. The difference between the jackknife alternative free-response receiver operating characteristic figure of merit at routine and lower-dose configurations was estimated. A lower 95% CI estimate of the difference greater than −0.10 indicated noninferiority.RESULTS: Forty-two of 83 patients had 70 intracranial findings (29 infarcts, 25 masses, 10 extra- and 6 intra-axial hemorrhages) at routine head CT (CT dose index = 38.3 mGy). The routine-dose jackknife alternative free-response receiver operating characteristic figure of merit was 0.87 (95% CI, 0.81–0.93). Noninferiority was shown for 100-effective mAs iterative reconstruction (figure of merit difference, −0.04; 95% CI, −0.08 to 0.004) and 200-effective mAs filtered back-projection (−0.02; 95% CI, −0.06 to 0.02) but not for 100-effective mAs filtered back-projection (−0.06; 95% CI, −0.10 to −0.02) or lower-dose levels. Image quality was better at higher-dose levels and with iterative reconstruction (P < .05).CONCLUSIONS: Observer performance for dose levels using 100–200 eff mAs was noninferior to that observed at 250 effective mAs with iterative reconstruction, with iterative reconstruction preserving noninferiority at a mean CT dose index of 15.2 mGy.CTDIvolvolume CT dose indexeff. mAseffective mAsFBPfiltered back-projectionGEEgeneralized estimating equationIRiterative reconstructionJAFROC FOMjackknife alternative free-response receiver operating characteristic figure of merit